Nothing about them without them: insights from six countries on involving “beneficiaries” in co-design, monitoring, and evaluation of research-to-impact projects - Zenebe Uraguchi (Frontiers in Sustainable Cities)
This study examines six participatory development cases situated in diverse institutional and sectoral contexts across Albania, Bangladesh, Ethiopia, Kosovo, the Philippines, and Tanzania. The study explores how systemic transformation emerges through co-design, adaptive learning, and institutional alignment,moving beyond linear input-output models of research impact. Using a developmental systems lens, the study treats impact not as a final result, but as a dynamic outcome shaped by the interplay of behavior, norms, and structures over time. Over 1,800 semi-structured interviews were triangulated with project documents, observational data, and binary logistic regression models to examine the influence of 10 participatory design features on sustained developmental outcomes. A key finding is that participation, particularly in monitoring, adaptive learning, and early framing, is not merely procedural but a systemic driver of institutional legitimacy, stakeholder trust, and long-term uptake. Countries with embedded participatory mechanisms, such as Ethiopia and Albania, showed deeper policy integration and structural change, while fragmented governance contexts, such as Tanzania and Kosovo, saw limited institutional embedding despite localized behavioral shifts. Crucially, the study argues that how research is done—who frames it, who participates in it, and how it adapts—is as consequential as what it seeks to achieve. Methodological integration of qualitative sensemaking and quantitative modeling offers practical insights into navigating complexity in research-to-impact pathways. Rather than serving as a report on six distinct cases, this article positions them as illustrations of a broader paradigm shift: from static, technocratic models to dynamic, participatory systems approaches. It offers both theoretical grounding and actionable guidance for researchers, implementers, and policymakers seeking to align evaluation and design with the realities of complex social systems.